Synthesis and characterization of organosoluble and transparent polyimides derived from trans‐1, 2‐bis(3, 4‐dicarboxyphenoxy)cyclohexane dianhydride. Issue 30 (29th April 2015) - Zhao, Huiwen; Chen, Guofei; Zhou, Yu; Li, Xing; Fang, Xingzhong
ABSTRACT A novel dianhydride, trans‐1, 2‐bis(3, 4‐dicarboxyphenoxy)cyclohexane dianhydride (1, 2‐CHDPA), was prepared through aromatic nucleophilic substitution reaction of 4‐nitrophthalonitrile with trans‐cyclohexane‐1, 2‐diol followed by hydrolysis and dehydration. A series of polyimides (PIs) were synthesized from one‐step polycondensation of 1, 2‐CHDPA with several aromatic diamines, such as 2, 2′‐bis(trifluoromethyl)biphenyl‐4, 4′‐diamine (TFDB), bis(4‐amino‐2‐trifluoromethylphenyl)ether (TFODA), 4, 4′‐diaminodiphenyl ether (ODA), 1, 4‐bis(4‐aminophenoxy)benzene (TPEQ), 4, 4′‐(1, 3‐phenylenedioxy)dianiline (TPER), 2, 2′‐bis[4‐(3‐aminodiphenoxy)phenyl]sulfone (m‐BAPS), and 2, 2′‐bis[4‐(4‐amino‐2‐trifluoromethylphenoxy)phenyl]sulfone (6F‐BAPS). The glass transition temperatures (Tgs) of the polymers were higher than 198°C, and the 5% weight loss temperatures (Td5%s) were in the range of 424–445°C in nitrogen and 415–430°C in air, respectively. All the PIs were endowed with high solubility in common organic solvents and could be cast into tough and flexible films, which exhibited good mechanical properties with tensile strengths of 76–105 MPa, elongations at break of 4.7–7.6%, and tensile moduli of 1.9–2.6 GPa. In particular, the PI films showed excellent optical transparency in the visible region with the cut‐off wavelengths of 369–375 nm owing to the introduction of trans‐1, 2‐cyclohexane moiety into the main chain. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42317.